The Analysis Types of Figurative Language Used in the Song Lyrics of Adele's Album “30” - Mahendra, I Komang Agus Tri; Suastini, Ni Wayan; Candra, Komang Dian Puspita (Institut Pariwisata dan Bisnis Internasional, 2024)
This study analyzes the figurative language used in the song lyrics of Adele’s album “30”. The song writer plays words and language to create attraction and distinctiveness towards the lyric of the song. Figurative language has the ability to be more impactful for the readers. This study is aimed to answer two problems of the study, they are: (1) To identify the types of figurative language used in the song lyrics of Adele's album